THE EFFECT OF TRAINING, MOTIVATION, CAREER DEVELOPMENT, AND JOB SATISFACTION ON THE PERFORMANCE OF PRODUCTION DEPARTMENT EMPLOYEES - Sri Langgeng Ratnasari; Lisvoni Saragih; T. Munzir; Gandhi Sutjahjo; Widyo Winarso (International Conference on Business Management and Accounting, 2022)
The purpose of this study was to determine and analyze the effect of training on employee performance, the effect of motivation on employee performance, the effect of career development on employee performance, the effect of job satisfaction on employee performance, and the effect of training, motivation, career development, and job satisfaction on employee performance. The population of this research is employees of PT. OZF as many as 105 people. The research sample was 105 respondents, using census sampling technique. Collecting data using a questionnaire. Data analysis using multiple linear regression and hypothesis testing using SPSS version 25. The results of the study are as follows: Training has a significant effect on employee performance, motivation has a significant effect on employee performance, career development has a significant effect on employee performance and job satisfaction has a significant effect on employee performance, and training, motivation, career development, and job satisfaction simultaneously affect employee performance.